2005
DOI: 10.1002/ana.20667
|View full text |Cite
|
Sign up to set email alerts
|

Model‐guided microarray implicates the retromer complex in Alzheimer's disease

Abstract: Although, in principle, gene expression profiling is well suited to isolate pathogenic molecules associated with Alzheimer's disease (AD), techniques such as microarray present unique analytic challenges when applied to disorders of the brain. Here, we addressed these challenges by first constructing a spatiotemporal model, predicting a priori how a molecule underlying AD should behave anatomically and over time. Then, guided by the model, we generated gene expression profiles of the entorhinal cortex and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
441
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 390 publications
(456 citation statements)
references
References 66 publications
14
441
0
1
Order By: Relevance
“…The finding that loss of PI(3,5)P 2 leads to neurodegeneration may be directly linked to recent discoveries that some forms of Alzheimer's disease correlate with defects in SORL1 (42) and Vps35 (43), which function in the same pathway. Vps35 is part of the retromer complex and in humans is required to form tubular carriers from the endosomes that travel by retrograde traffic to the trans-Golgi network (reviewed in ref.…”
Section: Discussionmentioning
confidence: 96%
“…The finding that loss of PI(3,5)P 2 leads to neurodegeneration may be directly linked to recent discoveries that some forms of Alzheimer's disease correlate with defects in SORL1 (42) and Vps35 (43), which function in the same pathway. Vps35 is part of the retromer complex and in humans is required to form tubular carriers from the endosomes that travel by retrograde traffic to the trans-Golgi network (reviewed in ref.…”
Section: Discussionmentioning
confidence: 96%
“…In attempting to address the analytic challenges of microarray, we were guided by our previous studies that used microarray to identify retromer trafficking defects as pathogenic in late-onset Alzheimer's disease (AD) (26,27). First, we needed to identify neighboring regions within the same brain structure, differentially affected and resistant to PD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our previous studies, imaging-guided microarray applied to AD identified deficiencies in the retromer trafficking pathway (27). However, only by systematically manipulating retromer-related molecules-in cell culture (27), animal models (26)-and by linking genetic variance to the disease in human patients (30), was this trafficking pathway pathogenically linked to AD (31).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the most disease-relevant among these trafficked proteins is APP. A few years ago, by using model-guided microarray techniques, our laboratory first identified deficiencies in the levels of the core retromer component Vps35 in the hippocampus of AD brains, suggesting a possible involvement of retromer function and trafficking in the pathogenic processing of APP [15]. In addition, protein levels of Vps26 were also reduced in the entorhinal cortex of patients with AD.…”
mentioning
confidence: 99%